2010
DOI: 10.1099/mic.0.033530-0
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans biofilm formation in a new in vivo rat model

Abstract: Device-associated microbial growth, including Candida biofilms, represents more than half of all human microbial infections and, despite a relatively small risk of implant-associated diseases, this type of infection usually leads to high morbidity, increased health-care costs and prolonged antimicrobial therapy. Animal models are needed to elucidate the complex host-pathogen interactions that occur during the development of attached and structured biofilm populations. We describe here a new in vivo model to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 37 publications
2
103
1
1
Order By: Relevance
“…To this end, we determined the miconazole sensitivity of biofilms of C. albicans mutants affected in cyclic AMP signalling, as it was previously reported that the cAMP signalling pathway is involved in the tolerance of planktonic C. albicans cells to miconazole (Jain et al, 2003). In addition, we validated the obtained in vitro data in an in vivo biofilm model, in which we administered miconazole intraperitoneally to rats (Ricicová et al, 2010). We finally demonstrated that by using miconazole as a model antimycotic compound, which is mainly used to treat topical fungal infections (Kyle & Dahl, 2004), these findings can be translated to other antimycotics such as amphotericin B (AmB) and caspofungin (CAS), which are used specifically in combatting systemic fungal infections (Kuhn et al, 2002a).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…To this end, we determined the miconazole sensitivity of biofilms of C. albicans mutants affected in cyclic AMP signalling, as it was previously reported that the cAMP signalling pathway is involved in the tolerance of planktonic C. albicans cells to miconazole (Jain et al, 2003). In addition, we validated the obtained in vitro data in an in vivo biofilm model, in which we administered miconazole intraperitoneally to rats (Ricicová et al, 2010). We finally demonstrated that by using miconazole as a model antimycotic compound, which is mainly used to treat topical fungal infections (Kyle & Dahl, 2004), these findings can be translated to other antimycotics such as amphotericin B (AmB) and caspofungin (CAS), which are used specifically in combatting systemic fungal infections (Kuhn et al, 2002a).…”
Section: Introductionmentioning
confidence: 89%
“…Control solution without miconazole was also prepared. In vivo biofilm drug susceptibility assays were determined using 1 cm pieces of serumcoated triple-lumen polyurethane catheters (Arrow International) as described previously (Ricicová et al, 2010). Briefly, animals were immunosuppressed 24 h prior to catheter implantation and throughout the whole experimental procedure (up to 9 days).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression data from planktonic culture or 24 h dispersal cells were used as reference samples to determine ΔΔ Ct values. The primers for ACT1 and were previously described by Řičicová et al [13]. The primers for CSH1 were designed by Dr.…”
Section: Quantitative Real Time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…The rat catheter biofilm infection model (Andes et al, 2004;Lazzell et al, 2009;Ricicová et al, 2010) allows evaluation in vivo of the comportment of one microorganism that is exposed to host proteins and immune factors. Other animal models have been utilized to monitor materials and devices that are placed in the bathing conditions of the oral cavity and to mimic denture stomatitis with fungal invasion and neutrophil infiltration of the adjacent mucosa.…”
Section: In Vivo Modelsmentioning
confidence: 99%